Hydrogen-bonded chains and networks of triptycene-based triboronic acid and tripyridinone - Zhang, Gang; Rominger, Frank; Mastalerz, Michael (Crystal growth & design, 2016)
The synthesis of 2,7,14-triptycene triboronic acid 1 and triptycene tripyridinone 2, as well as their packings in the crystalline states, was studied. Both compounds show pronounced aggregation by hydrogen bonding, thus forming supramolecular polymeric chains or interpenetrated networks depending on the solvent mixtures used for crystallization. In all examples, two of the three hydrogen bonding motifs in each molecule formed cyclic dimers, leaving the third site either masked by solvents or for the formation of another hydrogen bond with the dimeric units. The influence of the solvent is discussed.
Gesehen am 04.10.2021